Semi and continuous anaerobic treatment of palm oil mill effluent for the production of organic acids and polyhydroxyalkanoates - Hong, S. K.; Shirai, Yoshihito; Abdul Rahman, Nor'aini; Hassan, Mohd Ali (Academic Journals, 2009)
The aim of this study was to improve organic acids production in semi and continuous anaerobic treatment of Palm Oil Mill Effluent (POME) using a locally fabricated 50 L Continuously Stirred Tank Reactor (CSTR). The organic acids obtained were then used for polyhydroxyalkanoate (PHA) production by Ralstonia eutropha ATCC 17699 in a 2 L bioreactor. The conditions used in the anaerobic treatment were controlled pH 6.5, sludge to POME ratio at 1:1 and Hydraulic Retention Time (HRT) of 4 days. The organic acids obtained were about 15 g L-1 at steady state for both treatments and the organic acids yield (based on BOD) was 58.3%. The selected organic acids obtained were acetic (51.5%), propionic (27%) and butyric (21.5%) acid. The recovery of the clarified and concentrated organic acids from the treated POME was made using a two-steps evaporation process. The clarified organic acids (distillate) obtained were comprising of 44.6, 20.1 and 22.5 g L-1 acetic, propionic and butyric acids, respectively with a recovery of 76%. The organic acids collected were then used for polyhydroxyalkanoates accumulation by Ralstonia eutropha ATCC 17699 using pH stat fed-batch fermentation under nitrogen limitation of C/N 40 in a 2 L fermenter. The highest PHA concentration of 11.4 g L-1 (>90% w/w) was achieved in this process.